Vulnerability of Espionage Propaganda by Foreign Citizens (WNA) in Indonesia - Alfin Reza Syahputra; Muhammad Syaroni Rofii (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2022)
The development of cybercrime in several countries, especially regulations regarding espionage against foreigners. In the German Criminal Code they are called stragesetzbuches. This study discusses how propaganda is often carried out by unknown citizens. In Indonesia this vulnerability can be misinterpreted and suspected in terms of espionage. The purpose of this research is how to prevent espionage, especially by foreign nationals that occurs in Indonesia. The theory used is Cyber Intelligence Counter Operation Strategy. While the methodology used is qualitative in the process of obtaining data. In taking preventive and anticipatory actions against threats and disturbances to the security and order, so as to ensure the Sit. Kamtib properly requires the establishment and development of an early detection and warning system with functions in the intelligence domain with its parent. Intelligence must also build active and proactive communication with the widest community. The result of the research is to describe information on foreign nationals who enter the FPI (Islamic Defenders Front) base camp, which in this case is related to the issue of vulnerability to espionage propaganda in vulnerable issues in Indonesia at this time. So that solutions are needed for goodness and also the progress of security in Indonesia.